2021
DOI: 10.15586/ijfs.v33isp1.2059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural antioxidants and vegetable fiber on quality properties of fish sausage produced from Silver carp (Hypophthalmichthys molitrix)

Abstract: In this study, production of low-fat, nitrite-free sausage based on Silver carp surimi was performed. In order to replace oils, inulin fiber (IF) was used; natural preservatives such as grape pomace extract (GE) and nisin (NI) were used as nitrite replacements with modified atmosphere packaging (MAP: 70% CO2 + 30% N2). For this purpose; five treatments including, T1: control, T2: control + MAP, T3: IF 5% + MAP, T4: IF5% + GE0.5% + MAP, and T5: IF5% + GE0.5% + NI 0.5% + MAP, were prepared. The physicochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…At the beginning of the storage, the FFA levels for C-S, SK-S, and LS-S were 0.27 ± 0.04, 0.54 ± 0.06, and 0.36 ± 0.04% oleic acid, respectively. The lower FFA values in C-S might be attributed to the added inulin and polyphenol-rich spices which reduced the oxidative spoilage of the sausages . The higher initial (0th day) FFA value in SK-S is possibly due to the enzymatic and thermolytic hydrolysis along with the exposure to surrounding air during the process of kiln smoking .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…At the beginning of the storage, the FFA levels for C-S, SK-S, and LS-S were 0.27 ± 0.04, 0.54 ± 0.06, and 0.36 ± 0.04% oleic acid, respectively. The lower FFA values in C-S might be attributed to the added inulin and polyphenol-rich spices which reduced the oxidative spoilage of the sausages . The higher initial (0th day) FFA value in SK-S is possibly due to the enzymatic and thermolytic hydrolysis along with the exposure to surrounding air during the process of kiln smoking .…”
Section: Resultsmentioning
confidence: 98%
“…The lower FFA values in C-S might be attributed to the added inulin and polyphenol-rich spices which reduced the oxidative spoilage of the sausages. 56 The higher initial (0th day) FFA value in SK-S is possibly due to the enzymatic and thermolytic hydrolysis along with the exposure to surrounding air during the process of kiln smoking. 57 As the storage days advanced, the FFA values of C-S (1.29 ± 0.06%) and SK-S (1.18 ± 0.05%) sausages increased significantly ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…A great number of herbs and spices have the potential to delay lipid oxidation during food storage, usually mediated by the intrinsic antioxidant activities of their constituents. Lately, the use of natural antioxidants has increased in the food industry, and many studies have been reported on the subject (Delfino et al, 2021;Demir et al, 2014;Mahdavi and Ariaii, 2021;Messina et al, 2021;Özdemir et al, 2022;Rathod et al, 2021;Saati et al, 2022;Sengun et al, 2019;Trabelsi et al, 2021).…”
Section: Physical and Chemical Analysismentioning
confidence: 99%
“…Antioxidants usually provide preventive measures against the oxidation of lipids and protect against damages caused by free radicals. In the food industry, synthetic and natural antioxidants are commonly used to enhance the oxidation stability of different food products, such as edible oils (Erkan et al, 2008 ; Horrillo et al, 2022 ; Mahdavi & Ariaii, 2021 ). Research has proven that synthetic antioxidants have toxic and carcinogenic effects, and thus, many developed countries have opted to restrict the use of these antioxidants (Belmonte et al, 2021 ; González‐Montelongo et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%